Dysglycemia in young women attenuates the protective effect against fatty liver disease - Alejandra Pérez-Montes de Oca; Alejandra Pérez-Montes de Oca; María Teresa Julián; María Teresa Julián; Guillem Pera; Guillem Pera; Llorenç Caballería; Llorenç Caballería; Rosa Morillas; Rosa Morillas; Pere Torán; Pere Torán; et al. (Frontiers in Endocrinology, 2022)
IntroductionSexual dimorphism has been reported in non-alcoholic fatty liver disease (NAFLD), similar to the sex differences evident with cardiovascular disease. Type 2 diabetes mellitus (T2D) significantly increases the risk and severity of NAFLD, but there is scarce information on whether T2D or altered glucose metabolism can modify the prevalence of NAFLD in men and women of reproductive age.PurposeTo investigate the relationship between age, sex and NAFLD in subjects with and without dysglycemia.Materials and methodsWe analyzed 2,790 patients. NAFLD was characterized using established diagnostic criteria: one or more positive results on the fatty liver index and hepatic ultrasound. Liver fibrosis (liver stiffness measurement [LSM] ≥8.0 kPa) was assessed by Fibroscan®. For analysis purposes, we included both T2D and prediabetes under the predefined condition of dysglycemia.ResultsThe global prevalence of NAFLD was higher in men than in women (50% and 34%; P<0.001), and the prevalence increased with age in both sexes. Older women (≥ 50 years) had a higher prevalence than younger women (<50 years), both in the overall cohort and in non-dysglycemic subjects. In dysglycemic subjects, the prevalence of NAFLD was slightly higher in men (68% vs 61%, p=0.021); in younger subjects, there were no differences in the prevalence of NAFLD between men and women (68% vs 64%, respectively; p=0.635). We found an interaction between dysglycemia and female sex (odds ratio [OR] 1.6 95% confidence interval [CI] 1.0-2.4, p=0.030), and between and age ≥50 years (OR 0.6, 95% CI 0.3-1.0, p=0.046). The global prevalence of LSM ≥8.0 kPa was higher in men compared with women (8% vs 4%; p< 0.001). This prevalence increased with age, mainly in men. We did not find any association between liver fibrosis and age and gender.ConclusionsWhile the global prevalence of NAFLD is higher in men than in women across all ages, younger women with dysglycemia have a similar risk of developing NAFLD as men of a similar age. Therefore, the presence of dysglycemia may erase the protective effect of female sex against fatty liver disease.